Food physics : 10 fun physical science experiments. - Scientific American (COR) (New York : Scientific American Education Publishing in association with The Rosen Publishing Group, 2023)
Presents ideas for food experiments, including ideas for science fair projects.
Includes bibliographical references (page 63) and index.
Keywords: Food -- Experiments -- Juvenile literature; Science -- Experiments -- Juvenile literature; Food -- Experiments; Science -- Experiments